Topik-Topik dalam Buku Ajar BIPA Let’s Speak Indonesian: Ayo Berbahasa Indonesia 1 - Hanifia; Gatut Susanto; Ariva Luciandika (JoLLA: Journal of Language, Literature, and Arts, 2021)
Abstract: The Language Development and Cultivation Agency (2012) explains that BIPA is an Indonesian language learning process targeted to foreigners who are interested in learning Indonesian for a specific purpose. The process of learning Indonesian in general cannot be equated with learning Indonesian for foreign speakers. The textbook used contains materials used for teachers in implementing the learning process. The materials cover knowledge, skills that students must learn to achieve goals by competency standards. Because that's the use of language that suits the students' abilities. The purpose of this research is to describe the topics in the teaching material "Let's Speak Indonesia: Come on Indonesian Language 1". The data were obtained from the teaching materials contained in the teaching materials "Let's Speak Indonesia: Let's Speak Indonesian 1". With the data collected, researchers get the topics in textbooks. Based on the analysis of the topics used, it can support the learning process in the classroom and contains actual topics such as the environment, human relations, events. Presentation of topics in the teaching materials is in the form of verbal and visual. With a variety of presentation forms, the topic can be conveyed well. Keywords: BIPA, textbook, topic Abstrak: Badan Pengembangan dan Pembinaan Bahasa (2012) menjelaskan bahwa BIPA adalah proses pembelajaran bahasa Indonesia yang ditujukan kepada orang asing yang berminat mempelajari bahasa Indonesia untuk tujuan tertentu. Proses pembelajaran bahasa Indonesia pada umumnya tidak dapat disamakan dengan pembelajaran bahasa Indonesia bagi penutur asing. Buku teks yang digunakan berisi materi yang digunakan untuk guru dalam melaksanakan proses pembelajaran. Materi meliputi pengetahuan, keterampilan yang harus dipelajari siswa untuk mencapai tujuan sesuai standar kompetensi. Karena itulah penggunaan bahasa yang sesuai dengan kemampuan siswa. Tujuan dari penelitian ini adalah untuk mendeskripsikan topik-topik dalam bahan ajar “Ayo Bicara Indonesia: Ayo Bahasa Indonesia 1”. Data diperoleh dari bahan ajar yang terdapat pada bahan ajar “Ayo Bicara Indonesia: Mari Bicara Bahasa Indonesia 1”. Dengan data yang terkumpul, peneliti mendapatkan topik-topik dalam buku teks. Berdasarkan analisis topik yang digunakan dapat mendukung proses pembelajaran di kelas dan berisi topik aktual seperti lingkungan, hubungan manusia, peristiwa. Penyajian topik dalam bahan ajar dalam bentuk verbal dan visual. Dengan berbagai bentuk presentasi, topik dapat tersampaikan dengan baik. Kata kunci: BIPA, bahan ajar, topik